Integrasi nilai keislaman dalam total quality management untuk peningkatan mutu sekolah dasar: Integration of Islamic values in total quality management to improve the quality of elementary schools - Susilowati, Susilowati; Gumilar, Ricky; Masriah, Masriah; Karmini, Anis (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
The quality of education in Integrated Islamic Elementary Schools faces demands for adaptive, contextual, and continuous improvement in line with global dynamics and stakeholder needs. This study aims to analyze quality-control strategies grounded in Total Quality Management (TQM), operationalized through the PDCA cycle and integrated with Islamic values, at SDIT Fithrah Insani 2 Bandung. The methodology adopts a descriptive qualitative approach with a single-case study design; data were collected through interviews, observations, and institutional document analysis. The findings indicate three primary levers: (1) data-driven periodic evaluation in the Check-Act phase; (2) teacher–parent engagement that strengthens follow-up improvements; and (3) the internalization of the values of amanah (trustworthiness), honesty, and ihsan within instructional practice, which together enhance student learning outcomes and school–community collaboration. This study extends understanding of TQM in value-based education by showing that aligning quality strategies with an institution’s sociocultural characteristics is a prerequisite for effectiveness. The practical implications include designing a quality-control model responsive to local context and leveraging technology and community participation for a continuous feedback cycle, which is relevant for replication in similar schools.